Pendampingan Promosi Usaha Petani Sari Apel Di Desa Nongko Jajar Melalui Pemanfaatan Sosial Media/Marketplace Online - Mochamad Hasyim; Zainul Ahwan (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
Community service program on Assistance for Promotion of Apple Cider in Nongko Jajar Village Through the Utilization of Social Media/Marketplace Online has been carried out for approximately 2 months. This activity has contributed significantly to increasing new knowledge and skills for farmers Apples nongkojajar in promoting apple cider products through the utilization of online market places. In addition, the program partners also have trading accounts in the open marketplace and shopee stores as well as Facebook and Instagram social media. Through this effort apple farmers nongkojajar especially the program partners benefited from the service program conducted by the Communication Sciences lecturer team at Yudharta Pasuruan University. To encourage the sustainability of the program, the synergy between related parties becomes important to continue to be carried out such as the village/sub-district government, the department of communication and information, the Industry and Trade service provider and internet service providers and universities must be carried out with their respective functions and roles. Through this synergy it will encourage economic improvement and the welfare of apple farmers in Nongko Jajar.